Implikasi Hukum terhadap Akta Berita Acara Rapat Umum Pemegang Saham yang Dinyatakan Tidak Sah, Tidak Mengikat dan Batal Demi Hukum oleh Pengadilan - Chandra Handaru Baskara; Arief Suryono; Muhammad Rustamaji (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study examines the validity of the Minutes of the General Meeting of Shareholders (GMS) Deed and the legal implications arising when such deed is declared invalid, non-binding, or null and void. The study finds that the validity of an authentic deed depends on compliance with both the formal and substantive requirements governing its execution, as well as the conformity of the GMS procedures and resolutions with the company's Articles of Association and the Indonesian Company Law. Failure to satisfy these requirements may diminish the deed's evidentiary value and create legal uncertainty for the company, thereby requiring the restoration of the legal position to its original state.